1992
DOI: 10.1161/01.res.70.6.1233
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization and expression of functional and nonfunctional cell-to-cell channels from wild-type and mutant rat heart connexin43 cDNA.

Abstract: The carboxyl terminal cytoplasmic domain of distinct gap junction proteins may play an important role in assembly of functional channels as well as differential responsiveness to pH, voltage, and intracellular second messengers. Oligonucleotide-directed site-specific mutagenesis in a paired Xenopus laevis oocyte expression system was used to examine the expression of mRNAs encoding wild-type and carboxyl terminal mutant connexin43 (Cx43) proteins. Oocytes were stripped, injected with mRNA or distilled water (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 46 publications
2
36
0
Order By: Relevance
“…A Cx43-ZO-1 interaction has been identified at the cardiac intercalated disc and at gap junctions in testis, Rat-1 fibroblasts, lung epithelial cells, and astrocytes (23,28). ZO-1 binding is not essential for the formation of functional Cx43 channels, as evidenced by channel formation by Cx43 constructs lacking the carboxyl terminus (54,55); however, data suggest a possible involvement of ZO-1 in the localization of Cx43 to gap junction plaques (24) as well as in the process of internalization and remodeling of Cx43 upon changes in the intracellular environment (28,56). Another possible role for the Cx43CT-ZO-1 interaction is for ZO-1 to keep in close contact cellular partners that are important in the normal function of Cx43 gap junction channels.…”
Section: Discussionmentioning
confidence: 99%
“…A Cx43-ZO-1 interaction has been identified at the cardiac intercalated disc and at gap junctions in testis, Rat-1 fibroblasts, lung epithelial cells, and astrocytes (23,28). ZO-1 binding is not essential for the formation of functional Cx43 channels, as evidenced by channel formation by Cx43 constructs lacking the carboxyl terminus (54,55); however, data suggest a possible involvement of ZO-1 in the localization of Cx43 to gap junction plaques (24) as well as in the process of internalization and remodeling of Cx43 upon changes in the intracellular environment (28,56). Another possible role for the Cx43CT-ZO-1 interaction is for ZO-1 to keep in close contact cellular partners that are important in the normal function of Cx43 gap junction channels.…”
Section: Discussionmentioning
confidence: 99%
“…Truncation mutant M257 was a gift from Mario Delmar (State University of New York Upstate Medical University, Syracuse, NY). Deletion of 125 aa from the C terminal was achieved by replacing serine codon 257, TCA, with a stop codon, TGA (Dunham et al, 1992;Homma et al, 1998). Cx43-eGFP, Cx43 fused at its C terminus with enhanced green fluorescent protein (eGFP), was obtained from James Weiss (Cardiovascular Research Laboratory, University of California, Los Angeles, Los Angeles, CA) (John et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Although, evidence has been provided that ZO-1 is required for localization of Cx43 into gap junction plaques (Toyofuku et al, 1998), its presence is not essential for the formation of functional channels, because Cx43 constructs that lack the C-terminal region are able to form gap junction channels and plaques (Fishman et al, 1991;Dunham et al, 1992;Unger et al, 1999). Additional studies have shown that tagged Cxs are able to form gap junction plaques…”
Section: Introductionmentioning
confidence: 99%